The Role of the Institute for Political Studies in French-Serbian Scientific Cooperation and Cultural Diplomacy - Stojčić, Milica (Napredak, 2025)
The Francophonie is extremely important for the development not only of “cultural diplomacy”, but also of increasingly broader scientific cooperation, implementation of joint projects, activities and exchange of knowledge with the Republic of Serbia, as well as the whole region of the Western Balkans. The research is aimed at determining the scope, results as well as perspectives of the cooperation between the Institute for Political Studies, as one of the most outstanding actors in scientific, expert and cultural relations, and French scientific-research and educational institutions. In the research preparation, the author used the content analysis and limited observation with participation. In conclusion, Serbia is one of the key countries in the region for building scientific cooperation with France and, with rather limited funds allocated to social sciences and humanities en générale, the Institute for Political Studies manages to maintain the image of good partner through its exchange of knowledge, publications and implementation of joint project activities.
Keywords: French Republic; Republic of Serbia; Institute for Political Studies; cultural diplomacy; scientific cooperation